2017
DOI: 10.1080/01635581.2017.1367947
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Nutritional Status in Cancer: What is its Impact and how it Affects Disease Progression and Prognosis?

Abstract: Malnutrition is a common finding in cancer patients, which can affect disease progression and survival. This review aims to critically summarize the prognostic role of nutritional status, from Body Mass Index (BMI) and weight loss to nutrition screening tools and biochemical indices, in cancer patients. According to the currently available data, Prognostic Nutritional Index (PNI) was a significant prognostic factor of patients' survival, both in univariate and multivariate analyses. Pre-operative albumin was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
131
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 105 publications
4
131
0
4
Order By: Relevance
“…Malnutrition is a common phenomenon which can be found in cancer patients and previous evidence support that malnutrition was associated with worse outcomes . In the study conducted by Naito et al they defined CONUT score 5‐12 as malnutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a common phenomenon which can be found in cancer patients and previous evidence support that malnutrition was associated with worse outcomes . In the study conducted by Naito et al they defined CONUT score 5‐12 as malnutrition status.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to malnutrition, tumor cachexia, a complex multifactorial condition that arises from a combination of metabolic alterations, systemic inflammation, and decreased appetite, is also a major concern in patients with increased tumor burden [22]. Tumor cachexia is directly associated with malnutrition and associated with impaired wound healing, increased risk for surgical complications, and impaired overall outcome [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant reports have shown that the prognosis of tumor is closely related to the inflammatory status, immune function and nutritional status of patients (Mantzorou et al, 2017;Ni et al, 2019;Van Dijk & Pot, 2016;Xiao et al, 2019). Numerous studies have found that malnutrition significantly increases postoperative complications and has a negative impact on the quality of life, hospital stay, anti-cancer treatment effect and overall survival in cancer patients (Borre et al, 2018;Fujiya et al, 2018;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%